Epidemiology of pelvic fracture in the emergency room at Dr. Soetomo General Hospital between 2016-2018 - Yuga Ramadana; M Zaim Chilmi (Qanun Medika: Jurnal Kedokteran Fakultas Kedokteran Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT